Edukasi “GEMINSU”(Gemar Minum Susu) untuk Kesehatan Gigi Mulut di Masa Pertumbuhan - Sawitri Dwi Indah Pertami; Yolanda Kartika Asmarani; Rudi Irawan; Ige Frameski Radila Muga; Raden Aditya Wisnu Wardhana (Jurnal Medika: Medika, 2024)
The main problem of oral health in childhood is caries. Dental caries is caused by multifactorial factors including the host (tooth), substrate (food), microorganisms (bacteria) and time. Milk is a source of animal nutrition that is rich in calcium. Calcium plays an important role in the formation of dental hard tissue, making it more resistant to erosion and dental caries. By educating children at elementary school age to 'geminsu' love to drink milk can help children improve their ability to maintain oral health. This community service activity was carried out on students in grades 1-6 at SDN Lirboyo 1 Kediri City through several stages, namely pretest questionnaires, 'geminsu' education for oral health in infancy, posttest, door prize distribution, milk distribution, drinking milk together and group photos. The results of this community service showed that the percentage of knowledge about fond of drinking milk is important for oral health in infancy before education increased from 54% to 80%. The results of this service can be concluded that education on drinking milk can increase students' knowledge and awareness of the importance of milk for oral health during growth.